Task-Irrelevant Novel Sounds have Antithetical Effects on Visual Target Processing in Young and Old Adults - Tusch, Erich S.; Feng, Nicole C.; Holcomb, Phillip J.; Daffner, Kirk R. (Frontiers in Aging Neuroscience, 2017)
In young adults, primary visual task processing can be either enhanced or disrupted by novel auditory stimuli preceding target events, depending on task demands. Little is known about this phenomenon in older individuals, who, in general, are more susceptible to distraction. In the current study, age-related differences in the electrophysiological effects of task-irrelevant auditory stimuli on visual target processing were examined. Under both low and high primary task loads, the categorization/updating process in response to visual targets preceded by auditory novels, as indexed by the target P3 component, was enhanced in young, but diminished in old adults. In both age groups, the alerting/orienting response to novel auditory stimuli, as measured by the P3a, was smaller under high task load, whereas redirecting attention to the visual task after a novel auditory event, as indexed by the reorienting negativity (RON), tended to be augmented under high task load. Old subjects generated a smaller P3a and RON. We conclude that task irrelevant novel auditory stimuli have the opposite effect on the processing of visual targets in young and old adults. This finding may help explain age-related increases in the disruption of primary task activity by irrelevant, but salient auditory events.